FY15 Indonesia Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2016)
The Country Opinion Survey in Indonesia assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Indonesia perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Indonesia on 1) their views regarding the general environment in Indonesia; 2) their overall attitudes toward the WBG in Indonesia; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Indonesia; and 4) their perceptions of the WBG’s future role in Indonesia.